Desain dan Analisis Antena Mikrostrip Rectangular Dengan Slot “ m ” Untuk Aplikasi WLAN 2,4 GHZ - Nurista wahyu Kirana (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
Microstrip is being developed in various wireless applications, one of them is the WLAN (Wireless Local Area Network). In this study,  "m" slot was added to the center of the rectangular patch microstrip antenna which is designed using FR4 Epoxy material, also 2.4 GHz WLAN frequency band covered by the antenna. The thickness of the patch material is 1,5mm and the dielectric constant is 4,3. The Antenna is designed and simulated using CST Microwave Studio software. By changing the position of the microstrip antenna slot, several antenna parameter values were obtained including gain, return loss, bandwidth, and VSWR (Voltage Standing Wave Ratio). The microstrip antenna simulation results showed the best return loss value of -37.46 dB, VSWR of 1.027 at the resonant frequency of 2.446 GHz, and presented a gain of 3.43 dBi. From the results, the use of   "m" slot has several effecs of increasing the return loss value up to 42.63% and bandwidth by 5.17%.